Pengaruh Dividend Yield dan Earning Volatility terhadap Volativitas Harga Saham di Bursa Efek Jakarta - Rani Ramdhani (Binus Business Review, 2012)
Some investors prefer dividend yield than capital gain, information signal follows to dividend policy that describes the earnings volatility in the future, which affects the stock price volatility on the Jakarta Stock Exchange.